1985
DOI: 10.1002/ajh.2830180102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the measurement of surface or total platelet‐associated IgG in the diagnosis of immune thrombocytopenia

Abstract: Platelet-associated IgG (PAIgG) can be measured on intact platelets or following platelet lysis. Measurement of PAIgG following platelet lysis may provide different or additional information compared to PAIgG measured on intact platelets. The PAIgG of lysed platelets represents "total" PAIgG, ie, IgG on the surface of platelets plus any IgG that was inside the platelet. To investigate the clinical relevance of the two types of PAIgG assay we performed a prospective study on washed platelets collected from 47 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Normal controls, patients with ITP and non-immune thrombocytopenic patients are presented in relation to the upper normal ranges, 2 SD above the normal mean values. Reprinted with permission.26 per platelet.23 24 Despite the many different assays and reporting laboratories, there is remarkable agreement on this figure. It has been determined that the majority of PAIgG is found within a granules in the platelet and that less than 1 % is on the platelet surface.2' 22…”
Section: Total Platelet Associated Igg (Paigg)mentioning
confidence: 88%
“…Normal controls, patients with ITP and non-immune thrombocytopenic patients are presented in relation to the upper normal ranges, 2 SD above the normal mean values. Reprinted with permission.26 per platelet.23 24 Despite the many different assays and reporting laboratories, there is remarkable agreement on this figure. It has been determined that the majority of PAIgG is found within a granules in the platelet and that less than 1 % is on the platelet surface.2' 22…”
Section: Total Platelet Associated Igg (Paigg)mentioning
confidence: 88%
“…This assay was performed using an immunoradiometric (IRMA) assay described previously (Kelton et al, 1985). A standard curve was generated by testing dilutions of pre-quantitated IgG in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…Phase II assays were designed to measure either surface or total PAIgG [7,8]. However, it was later shown that PAIgG was elevated in a wide spectrum of nonimmune TP disorders.…”
Section: Introductionmentioning
confidence: 99%